Social networks, entrepreneurship and modernity : evidence from a historical episode of industrialization (2016)
This paper explores the role of social networks in the emergence of industrial entrepreneurship. lt uses evidence from Colombia in the late 19th and early 20th century. lt finds that the social capital related with structural holes did have significant and positive effects on industrial entrepreneurship. Meanwhile, the social capital related with closure did not have significant positive effects. In fact, higher density in certain networks, like family networks, reduced industrial entrepreneurship. Through this exercise, the paper shed light on how social capital might promote modernity under weak institutional environments.